MONITORING LOAD IMBALANCE IN DISTRIBUTION TRANSFORMER PT. PLN ULP TULEHU BASED ON THE INTERNET OF THINGS (IOT) - ARI PERMANA; SOLEMAN SESA (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2022)
Distribution transformer maintenance is an important thing to keep the transformer operating optimally, one of which is by monitoring load imbalance and overload on the distribution transformer. Load imbalance is a condition where the electrical loads connected to each phase of the distribution transformer are not the same size. At PT PLN ULP Tulehu, the transformer load measurement activities are still carried out manually, the tool used by officers in measuring the distribution transformer load is ampere pliers and is carried out once every six months. This shows that substation load monitoring is still done manually or not in Real Time so that monitoring results cannot be monitored in a short span of time. As a result, disturbances in the transformer cannot be known early on. The location of transformers that are scattered in various locations can also be an obstacle for officers to be able to measure loads on time, allowing the risk of transformers being damaged more. This research aims to assist officers in monitoring imbalances and overloads on distribution transformers remotely. The monitoring tool uses the Pzem-016T sensor by measuring electrical parameters such as current, voltage, frequency, load imbalance presentation and used load presentation then the measurement data is monitored in the Blynk application. The test results show that the monitoring equipment is able to work well to read the condition of load imbalance and transformer used load remotely. This monitoring tool has a deviation value (error) of the design measuring instrument against the standard measuring instrument is 0.68% for R-N voltage (volts), 0.76% for S-N voltage (volts), 0.15% for T-N voltage (volts), 0.38% for IR current (amperes), 0.52% for IS current (amperes), 0.81% for IT current (amperes)